Assessing sustainability hotspots in the production of paper-based printed electronics. (1st March 2023) - Sudheshwar, Akshat; Beni, Valerio; Malinverno, Nadia; Hischier, Roland; Nevo, Yuval; Dhuiège, Benjamin; Borras, Mateu; Chbani, Aiman; Aucher, Christophe; Martinez-Crespiera, Sandra; Eibensteiner, Friedrich; Kurzhals, Steffen; et al.
Abstract: Novel printed electronics are projected to grow and be manufactured in the future in large volumes. In many applications, printed electronics are envisaged as sustainable alternatives to conventional (PCB-based) electronics. One such application is in the semi-quantitative drug detection and point-of-care device called 'GREENSENSE' that uses paper-based printed electronics. This paper analyses the carbon footprint of GREENSENSE in order to identify and suggest means of mitigating disproportionately high environmental impacts, labeled 'sustainability hotspots', from materials and processes used during production which would be relevant in high-volume applications. Firstly, a life cycle model traces the flow of raw materials (such as paper, CNCs, and nanosilver) through the three 'umbrella' processes (circuit printing, component mounting, and biofunctionalization) manufacturing different electronic components (the substrate, conductive inks, energy sources, display, etc) that are further assembled into GREENSENSE. Based on the life cycle model, life cycle inventories are modeled that map out the network of material and energy flow throughout the production of GREENSENSE. Finally, from the environmental impact and sustainability hotspot analysis, both crystalline nanocellulose and nanosilver were found to create material hotspots and they should be replaced in favor of lower-impact materials. Process hotspots are created by manual, lab-, and pilot-scale processes with unoptimized material consumption, energy use, and waste generation; automated and industrial-scale manufacturing can mitigate such process hotspots.